Economic valuation of environmental benefits in developing and emerging countries: Theoretical considerations and practical evidence from Thailand and the Philippines - Michael Ahlheim (2018)
The contingent valuation method (CVM) for assessing the social value of environmental benefits accruing from public projects has gained increasing popularity also in developing and emerging countries. In CVM studies, the social value of a project is typically assessed as the aggregate willingness to pay of the affected households for this project. However, the transferability of this method from the socio-economic context of industrialized countries, where it was originally applied, to developing and emerging countries must be scrutinized. This paper highlights a number of problematic issues that arise in the context of applying the CVM in developing and emerging countries. The theoretical considerations are exemplified by two practical valuation studies conducted in northern Thailand as a representative of an emerging country and in a rural area of the Philippines as a representative of a developing country.